Whole Body Vibration Analysis of Baby Hammock - Ko Ying Hao; Geh Chia Sin (MATEC Web of Conferences, 2018)
Studies have been carried on the effect of rocking on a baby and concluded that baby sleeps easier while being rocked. In Malaysia, as in many Southeast Asian Countries, it is common to put babies to sleep in a baby hammock. the vertical rocking motion generated by baby hammock has exposed babies to whole-body vibration (WBV). It has been shown by ISO2631 (1997) that WBV may lead the discomfort and adverse effect on health. Standards have been set by ISO 2631 (1997) concerning the WBV for people in a recumbent position and consider weighted vibrations of more than 2 m/s2 to be extremely uncomfortable. However, standards concerning the allowable amount vibrations a baby in a baby hammock can safety endure are currently lacking. WBV analysis of the baby hammock with the weight ranged from 3kg to 14kg is conducted. For each measurement, four conditions are considered: manual rocking, auto rocking with low, medium and high speed. In this study, average root-mean-square values for the acceleration were found to be at a maximum of 2.46 m/s2, and to be above the extremely uncomfortable level. This study develops a baseline exposure time for the baby hammock before it reaches the safety values of exposure action value (EAV) and exposure limit value (ELV) set by ISO 2631(1997).